Chlorogenic Acid Decreases Malignant Characteristics of Hepatocellular Carcinoma Cells by Inhibiting DNMT1 Expression - Yao Liu; Ying Feng; Yuxin Li; Ying Hu; Qun Zhang; Yunyi Huang; Ke Shi; Chongping Ran; Jie Hou; Guiqin Zhou; Xianbo Wang (Frontiers Media S.A., 2020)
BackgroundHepatocellular carcinoma (HCC) is the most common malignant tumor of the adult liver, exhibiting rapid progression and poor prognosis. Chlorogenic acid (CGA), a polyphenol, has several biological activities, including the suppression of liver cancer cell invasion and metastasis. Increased levels or alterations in the function of DNMT1 are associated with the inactivation of tumor suppressor genes. However, the CGA-affected DNMT1 expression mediated mechanism is still unclear.MethodsThe human hepatocellular carcinoma (HCC) HepG2 cells were treated with a positive control drug (5-AZA) or varying doses of CGA. DNA methyltransferase 1 (DNMT1) protein levels and other relevant proteins were evaluated using Western blotting and immunocytochemistry. Cell-cycle analysis was performed by flow cytometry-based PI staining, and cell viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The transwell invasion and wound healing assays were used to evaluate cell migration and invasion. In vivo proliferation of the HCC cells was detected. We investigated the expression of DNMT1, p53, p21, p-ERK, MMP-2, and MMP-9 in tumors using immunohistochemical analysis.ResultsOur results showed that CGA inhibited the proliferation, colony formation, invasion, and metastasis of HepG2 cells both in vitro and in vivo by down-regulating DNMT1 protein expression, which enhanced p53 and p21 activity, and resulting in a significant reduction in cell proliferation and metastasis. Moreover, CGA inactivated ERK1/2 and reduced MMP-2 and MMP-9 expression in HepG2 cells.ConclusionsCGA can suppress liver cancer cell proliferation, invasion, and metastasis through several pathways. CGA could serve as a candidate chemopreventive agent for HCC.